Penerapan Teori Belajar Behaviorisme untuk Meningkatkan Keterlibatan Siswa dalam Pembelajaran Matematika : Studi Kasus Barisan dan Deret Aritmatika pada Kelas 10 SMK Karya Serdang Lubuk Pakam - Alya Anggriani Sinaga; Fery Sinabutar; Nia Novita Insani Sinaga; Putri Arga L. Munthe; Sabrina Nur Karimah Nst (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2025)
This study aims to examine the application of behaviorism learning theory in enhancing student engagement in mathematics learning, particularly arithmetic sequences and series. The study was conducted at SMK Karya Serdang Lubuk Pakam with 24 tenth-grade students in a single meeting on September 17, 2025. The research team delivered the material, provided stimulus in the form of problems written on the board, and applied positive reinforcement by giving rewards to students who dared to and successfully answered. Data were collected through observation, field notes, and brief interviews. The results showed a significant increase in student engagement: more students volunteered to solve problems on the board, the classroom atmosphere became more lively, and participation in discussions improved. Although some students remained hesitant, the behaviorist strategy proved effective in enhancing motivation and engagement. These findings reinforce the theories of Thorndike, Pavlov, and Skinner, which emphasize the stimulus–response relationship and reinforcement as the basis of learning (Hamruni et al., 2021; Yusup, 2024).